2007
DOI: 10.1016/j.jmgm.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of the Journal of Molecular Graphics and Modelling

Abstract: Abstract. This paper reviews the articles published in Volumes 2-24 of the Journal of Molecular Graphics and Modelling (formerly the Journal of Molecular Graphics), focusing on the changes that have occurred in the subject over the years, and on the most productive and most cited authors and institutions. The most cited papers are those describing systems or algorithms, but the proportion of these types of article is decreasing as more applications of molecular graphics and molecular modelling are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…For instance, bibliometric studies have focused on identifying the main authors in a field (Willett, 2007), the impact of a scholar in the discipline (Ferreira, 2011), the impact of a journal (Tahai & Meyer, 1999), the stock of knowledge in one domain (Ferreira et al, 2014), and the intellectual structure of a discipline such as strategic management (Ramos-Rodriguez & Ruiz-Navarro, 2004) and knowledge management (Ponzi, 2002). All these studies rely on different forms of examining citations and co-citations as primary inputs from a bibliographic dataset.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, bibliometric studies have focused on identifying the main authors in a field (Willett, 2007), the impact of a scholar in the discipline (Ferreira, 2011), the impact of a journal (Tahai & Meyer, 1999), the stock of knowledge in one domain (Ferreira et al, 2014), and the intellectual structure of a discipline such as strategic management (Ramos-Rodriguez & Ruiz-Navarro, 2004) and knowledge management (Ponzi, 2002). All these studies rely on different forms of examining citations and co-citations as primary inputs from a bibliographic dataset.…”
Section: Methodsmentioning
confidence: 99%
“…In all, the 20 articles attracted 9301 citations, i.e., 29.8% of the total number of citations to the journal. As has been noted in previous studies [5,7], descriptions of chemoinformatics methods or systems can rapidly attract very large numbers of citations if an article becomes the "standard" reference, i.e., the one that is normally cited when a particular algorithm or piece of software is used in a project. This is again the case here, with descriptions of DISCO, DOCK, GASP, LUDI, MOLDEN and MOPAC appearing amongst the 20 most-cited JCAMD articles that are listed in Table 1; descriptions of CAVEAT, CoMSIA, IsoStar and SPROUT inter alia appear as one moves further down the list of highly-cited articles.…”
Section: Citations To the Journalmentioning
confidence: 98%
“…Such bibliometric studies of journals have been reported in very many disciplines [4] including, recently, computer-aided drug discovery [5][6][7]. The data for the present study was obtained from the Web of Science, a database from Thomson Reuters that contains the publications in, and the citations to, ca.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have also made other contributions, e.g., in the application of chemoinformatics techniques to the representation and searching of biological macromolecules such as protein and RNA structures, [71][72][73][74][75] in the analysis of matched molecular pairs [76] and in charting the historical development of chemoinformatics and of its associated literature. [77][78][79][80] We have also sought to influence the development of the field by means of conferences and educational programmes. Thus, in 1998 we were invited by the Chemical Structure Association Trust This paper has focused on research in Sheffield, but we have also been active in teaching the subject; indeed, arguably the very first textbook in the field was based on material taught in a one-semester module that Lynch developed shortly after coming to Sheffield.…”
Section: Other Contributionsmentioning
confidence: 99%